Oxysterole-binding protein targeted by SARS-CoV-2 viral proteins regulates coronavirus replication - Ma-Lauer, Yue; Li, Pengyuan; Niemeyer, Daniela; Richter, Anja; Pusl, Konstantin; von Brunn, Brigitte; Ru, Yi; Xiang, Chengyu; Schwinghammer, Sebastian; Liu, Jia; Baral, Priya; Berthold, Emilia J.; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction Oxysterol-binding protein (OSBP) is known for its crucial role in lipid transport, facilitating cholesterol exchange between the Golgi apparatus and endoplasmic reticulum membranes. Despite its established function in cellular processes, its involvement in coronavirus replication remains unclear. Methods In this study, we investigated the role of OSBP in coronavirus replication and explored the potential of a novel OSBP-binding compound, ZJ-1, as an antiviral agent against coronaviruses, including SARS-CoV-2. We utilized a combination of biochemical and cellular assays to elucidate the interactions between OSBP and SARS-CoV-2 non-structural proteins (Nsps) and other viral proteins. Results Our findings demonstrate that OSBP positively regulates coronavirus replication. Moreover, treatment with ZJ-1 resulted in reduced OSBP levels and exhibited potent antiviral effects against multiple coronaviruses. Through our investigation, we identified specific interactions between OSBP and SARS-CoV-2 Nsps, particularly Nsp3, Nsp4, and Nsp6, which are involved in double-membrane vesicle formation—a crucial step in viral replication. Additionally, we observed that Nsp3 a.a.1–1363, Nsp4, and Nsp6 target vesicle-associated membrane protein (VAMP)-associated protein B (VAP-B), which anchors OSBP to the ER membrane. Interestingly, the interaction between OSBP and VAP-B is disrupted by Nsp3 a.a.1–1363 and partially impaired by Nsp6. Furthermore, we identified SARS-CoV-2 orf7a, orf7b, and orf3a as additional OSBP targets, with OSBP contributing to their stabilization. Conclusion Our study highlights the significance of OSBP in coronavirus replication and identifies it as a promising target for the development of antiviral therapies against SARS-CoV-2 and other coronaviruses. These findings underscore the potential of OSBP-targeted interventions in combating coronavirus infections.